Is the mandibular growth affected by internal rigid fixation?: A systematic review (2017)
Purpose The purpose of this systematic review was to evaluate, in animal model-based studies, whether there are mandibular growth alterations, after open reduction and internal rigid fixation with titanium plates and screws. Methods A literature search was conducted using the MEDLINE, EMBASE, and LILACS databases, up to and including August 2015. Surgical reduction and internal rigid fixation (IRF) of induced fractures were compared to non-invasive procedures, in order to investigate if there were alterations in the mandibular growth patterns. Results Of a total of 624 potentially relevant papers identified through the searching process, five were eligible for inclusion. Three studies using 3-month old New Zealand white rabbits induced fractures of mandibular body or symphysis and internal fixation with titanium microplates and screws, whereas two were based on 6-month old goats with condylar fracture. None of the studies showed statistically significant difference between experimental and control groups. Conclusion As literature regarding this subject is scarce, and the included studies show low level of evidence, it is not possible to conclude that open reduction and internal rigid fixation with titanium plates and screws cause significant growing alteration of the mandible.